2019
DOI: 10.3866/pku.whxb201901002
|View full text |Cite
|
Sign up to set email alerts
|

Toward Improved Thermal Conductance of Graphene-Polyethylene Composites <i>via</i> Surface Defect Engineering: a Molecular Dynamics Study

Abstract: Polymers are widely used advanced materials composed of macromolecular chains, which can be found in materials used in our daily life. Polymer materials have been employed in many energy and electronic applications such as energy harvesting devices, energy storage devices, light emitting and sensing devices, and flexible energy and electronic devices. The microscopic morphologies and electrical properties of the polymer materials can be tuned by molecular engineering, which could improve the device performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…Similarly, Achadu et al group used GO as a SERS-active substrate and molybdenum trioxide nanocube as a SERS nanotag to construct an immunosensor for norovirus detection. Due to the synergistic effect of SERS substrate and nanotag, this proposed immunosensor obtained a ~10 9 -fold signal amplification, resulting in an ultralow detection limit for norovirus detection (~5.2 fg•mL −1 ). It should be noted that this immunosensor can determine as low as ~60 RNA copy•mL −1 in human fecal samples, which is much lower than that of a commercial kit 1403 .…”
Section: Spr Sensing Platformsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Achadu et al group used GO as a SERS-active substrate and molybdenum trioxide nanocube as a SERS nanotag to construct an immunosensor for norovirus detection. Due to the synergistic effect of SERS substrate and nanotag, this proposed immunosensor obtained a ~10 9 -fold signal amplification, resulting in an ultralow detection limit for norovirus detection (~5.2 fg•mL −1 ). It should be noted that this immunosensor can determine as low as ~60 RNA copy•mL −1 in human fecal samples, which is much lower than that of a commercial kit 1403 .…”
Section: Spr Sensing Platformsmentioning
confidence: 99%
“…This can be solved by fabricating heterostructures with strong built-in electric fields easily. Hu et al reported that PdSe2/MoS2 based photodetector shows a fast response rate of 51.3 μs and a high detectivity as 10 9 Jones even for 10.6 μm LWIR detection 856 . Also, the ballistic avalanche phenomenon was observed in vertical InSe/BP heterostructures with suitable thickness.…”
Section: D Heterostructures For Optoelectronicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the thermal transport behavior of the graphene−water interface is specifically studied in our simulations, the analysis of thermal conductance is more appropriate to transparentize the thermal coupling compared with thermal conductivity. 34 A moderate temperature drop is applied to calculate thermal conductance since a large temperature drop could induce a nonlinear effect while a small one would lead to large uncertainty due to temperature fluctuation. 35 To minimize the statistical uncertainty in simulations, the results were averaged over five individual simulations with different initial velocity seeds.…”
Section: Computational Model and Detailsmentioning
confidence: 99%
“…However, most polymers exhibit typically poor thermal conductivity, such as the thermal conductivity of polyvinylidene fluoride (PVDF), polydimethylsiloxane (PDMS), polystyrene (PS), etc., ranging from 0.1 to 0.4 W m −1 K −1 [15], which significantly limits their applications as TIMs. In order to solve this problem, functional fillers of different shapes and types with high thermal conductivity are added into polymers to improve the heat transportation efficiency [16][17][18][19][20][21][22][23]. Wang et al enhanced the thermal conductivity of carbon fiber/polymer composites through SiC nanowires/graphene hybrid nanofillers [24].…”
Section: Introductionmentioning
confidence: 99%